Investigating the Potential for Collaboration Between Translators and Filmmakers in the Subtitling of Foreign Films: A Qualitative Exploration of Views - Nettelbeck, Hugh Wilson (Journal of Audiovisual Translation, 2024)
Collaboration between filmmakers and subtitlers should result in subtitles that better reflect filmmakers’ intentions. However, these parties rarely communicate in practice, and not enough research has been conducted to investigate attitudes towards collaboration among both parties. Interviews were conducted with 12 professional subtitlers and eight filmmakers to investigate attitudes to and prior experience of collaborating on subtitles. Attitudes varied between parties. Filmmakers were generally enthusiastic about past collaborations, whereas subtitlers’ opinions were mixed. Some subtitlers noted collaboration helped understand filmmakers’ intent for dialogue. Conversely, others reported input from filmmakers could be overbearing and unhelpful. Some subtitlers doubted filmmakers would be interested in subtitling, despite filmmakers’ largely positive attitudes to collaboration. Both groups expressed concerns about time and monetary costs. Interviewees also indicated concerns about when, in the filmmaking process, collaboration would be most useful, with some disputing the practicality of Romero-Fresco’s (2019) accessible filmmaking model, which includes collaboration from pre-production to post-production. Both parties viewed subtitling as a creative process, which might be facilitated by collaboration, depending on the product being subtitled. Given subtitlers’ higher scepticism towards collaboration, it is likely that an acceptable collaborative model would be subtitler-initiated and limited to post-production, although further research is required. Lay summary Collaboration between filmmakers and subtitlers should result in subtitles that are closer to filmmakers’ intentions. However, these two groups rarely communicate in practice, and not enough research has looked at attitudes towards collaboration among both parties. I interviewed 12 professional subtitlers and eight filmmakers to investigate opinions on the pros and cons of working together during the creation of subtitles. Attitudes differed between the two groups. Filmmakers were generally enthusiastic about past collaborations, whereas subtitlers’ opinions were mixed. Some subtitlers noted collaboration helped them to understand filmmakers’ intent for dialogue. On the other hand, other subtitlers said that input from filmmakers could be overbearing and unhelpful. Some subtitlers doubted filmmakers would be interested in subtitling, despite filmmakers’ largely positive attitudes to collaboration. Both groups expressed concerns about time and money. Interviewees also indicated concerns about when, in the filmmaking process, collaboration would be most useful. Both parties viewed subtitling as a creative process, which might benefit from collaboration, depending on the film or show being subtitled. Given subtitlers’ higher scepticism towards collaboration, it is likely that collaboration between these two groups would work best if it was initiated by the subtitler and limited to the post-production stage, although further research is required.